2014
DOI: 10.1890/es14-00296.1
|View full text |Cite
|
Sign up to set email alerts
|

Topography alters tree growth–climate relationships in a semi‐arid forested catchment

Abstract: Abstract. Topography and climate play an integral role in the spatial variability and annual dynamics of aboveground carbon sequestration. Despite knowledge of vegetation-climate-topography relationships on the landscape and hillslope scales, little is known about the influence of complex terrain coupled with hydrologic and topoclimatic variation on tree growth and physiology at the catchment scale. Climate change predictions for the semi-arid, western United States include increased temperatures, more frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 50 publications
8
75
0
Order By: Relevance
“…We did not assess conifer stemwood response to interannual climate variability. However, our findings generally concur with the conclusions of Bunn et al (), Anning et al (), and Adams et al (), who observed differential conifer response to temperature and precipitation dynamics based on site moisture conditions. Bunn et al () found that P. balfouriana growing in divergent and high radiation settings were more sensitive to interannual patterns of precipitation than those in convergent, low radiation settings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We did not assess conifer stemwood response to interannual climate variability. However, our findings generally concur with the conclusions of Bunn et al (), Anning et al (), and Adams et al (), who observed differential conifer response to temperature and precipitation dynamics based on site moisture conditions. Bunn et al () found that P. balfouriana growing in divergent and high radiation settings were more sensitive to interannual patterns of precipitation than those in convergent, low radiation settings.…”
Section: Discussionsupporting
confidence: 93%
“…Further, Anning et al () found that conifers in mesic sites had substantially less significant correlations with climatic variables than those in intermediate and xeric sites. Similarly, Adams et al () observed variability of conifer response to interannual precipitation and temperature regimes when stems were positioned in low versus high TWI locations, suggesting that topography altered conifer growth response to climate. For example, P. ponderosa and P. contorta were less responsive to warm temperatures and P. ponderosa was less responsive to precipitation patterns when located in wet landscape positions.…”
Section: Discussionmentioning
confidence: 83%
“…It is well known that due to their influence on water runoff and wind exposition, topographic factors such as slope and aspect can critically affect tree growth and forest productivity (Adams, Barnard, & Loomis, ; Fekedulegn, Hicks, & Colbert, ). To our knowledge, this is the first study demonstrating that topographic characteristics can also induce changes in complementarity effects, although a general trend across species and mixture types could not be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the topographic effects on water redistribution could enhance or inhibit hydrological and biogeochemical processes, creating biogeochemical hot-spots in the wettest locations (McClain et al 2003). Therefore, taking topography into account could both improve our understanding of hydrological and biogeochemical linkages and provide an explanation for emerging spatial patterns (e.g., Adams et al 2014). Moreover, topographic features and their spatial distribution are key to scale-up plot-based knowledge to the landscape level (e.g., Riveros-Iregui and McGlynn 2009, Vico and Porporato 2009, Riveros-Iregui et al 2011.…”
Section: Cross-scale Connectivitymentioning
confidence: 99%